2016
DOI: 10.1093/nar/gkw825
|View full text |Cite
|
Sign up to set email alerts
|

A small stem-loop structure of the Ebola virus trailer is essential for replication and interacts with heat-shock protein A8

Abstract: Ebola virus (EBOV) is a single-stranded negative-sense RNA virus belonging to the Filoviridae family. The leader and trailer non-coding regions of the EBOV genome likely regulate its transcription, replication, and progeny genome packaging. We investigated the cis-acting RNA signals involved in RNA–RNA and RNA–protein interactions that regulate replication of eGFP-encoding EBOV minigenomic RNA and identified heat shock cognate protein family A (HSC70) member 8 (HSPA8) as an EBOV trailer-interacting host protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
(92 reference statements)
1
16
0
Order By: Relevance
“…S2eS19). Sequence analysis showed that the nucleic acid of Ebolavirus (EBOV, SUDV, RESTV, TAFV) between their 3 0 terminal (18 nt) and 5 0 terminal (20 nt) were highly identical [42], and conserved stem-loop structures were found [42,44,45], which proved the accuracy of the prediction results in this study. Here, we displayed the relationship between such structures and microsatellites to speculate on the role of microsatellites in Ebolavirus genome.…”
Section: Conserved Microsatellites May Contribute To Conserved Stemlosupporting
confidence: 71%
See 1 more Smart Citation
“…S2eS19). Sequence analysis showed that the nucleic acid of Ebolavirus (EBOV, SUDV, RESTV, TAFV) between their 3 0 terminal (18 nt) and 5 0 terminal (20 nt) were highly identical [42], and conserved stem-loop structures were found [42,44,45], which proved the accuracy of the prediction results in this study. Here, we displayed the relationship between such structures and microsatellites to speculate on the role of microsatellites in Ebolavirus genome.…”
Section: Conserved Microsatellites May Contribute To Conserved Stemlosupporting
confidence: 71%
“…The 5 0 , 3 0 terminal non-coding regions were thought to regulate viral transcription, replication, and assembly of new virions [23]. The 3 0 trailer of Ebolavirus were essential for replication by formed a small stem-loop structure, and participated in RNA-Protein interaction [44]. The related results suggested that conserved microsatellites in the terminal regions of Ebolavirus were well base-paired to help forming conserved stem-loop structures ( Fig.…”
Section: Conserved Microsatellites May Contribute To Conserved Stemlomentioning
confidence: 98%
“…For example, an important cis -acting RNA structure required for EBOV transcriptional regulation is located in the 3′ extracistronic region of the viral genome and functions through interaction with the viral trans -acting factor, VP30 ( 18 21 ). Nevertheless, functionality of most EBOV RNA secondary structures and potential host or viral trans -acting factors that recognize these structures have not been well established ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long-range interactions have also been identified in the negative-sense RNA genome of Ebola virus (EBOV), a filovirus that causes Ebola hemorrhagic fever in humans and other mammals (Sztuba-Solinska et al, 2013 ). This section will highlight two studies in which 5′-3′ interactions in DENV and EBOV were characterized using capillary electrophoresis-based SHAPE (CE-SHAPE) and complementary biochemical techniques (Sztuba-Solinska et al, 2013 , 2016 ).…”
Section: Characterization Of Long-range Viral Rna Interactions Is Facmentioning
confidence: 99%